An analytical fit and EGSnrc code (MC) calculations of personal dose equivalent conversion coefficients for mono-energetic electrons. (December 2019) - Al Kanti, Hassan; El Hajjaji, O.; El Bardouni, T.; Mohammed, Maged
Abstract: This study aims for calculating a new set of the personal dose equivalent conversion coefficients H p ( d)/Φ when d = 0.07, 3, and 10 mm, for mono-energetic electron beams ranged from 0.06 MeV to 50 MeV for H p ( 0.07), from 0.7 MeV to 50 MeV for H p (3) and from 2 MeV to 50 MeV for H p ( 10), which has incident on ICRU slab phantom. Additionally, we have calculated the conversion coefficients of a dose to the lens eye of into a new cylindrical phantom of the ORAMED project. The cylindrical phantom was proposed for calculating the eye lens dose equivalent as a cylinder much better approximates the form of a head than a slab. The ICRU tissue of density of 1 g/cm 3 which is consists of 4-elemental has been used in slab and cylindrical phantoms. The calculations were carried out with EGSnrc code Monte Carlo (MC) and a new an analytical fit is applied to the data. Our results are found in a good agreement with those published by Veinot and Hertel (2012)), with a local difference less than 1.5%. We have concluded that new analytical fits provide a convenient approach for determining conversion coefficients for discrete incident such as MC. Highlights: A new analytical fit provides a convenient approach for determining conversion coefficients. EGSnrc code has been validated in a new phantom cylinder of the ORAMED project. Must protect the skin, the lens of the eye and human body at the energies 0.1, 1.5, 4 MeV for electrons, respectively. A good agreement between our results with those published by Veinot and Hertel (2012).